As ciências humanas nas redes sociais: o uso do instagram como ferramenta de divulgação científica - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This research analyzed the scientific dissemination of the Humanities on Instagram, considering social media as central contemporary spaces for sociability, information, and non-formal education. Starting from the conception of science communication as the recoding of academic language for a lay audience, the study sought to identify which formats and types of content are most commonly used and generate the highest engagement on Instagram. To achieve this, posts from communicators in the fields of History, Geography, Sociology, and Philosophy were analyzed, selected based on rel evance and posting frequency. The methodology used was content analysis, with posts categorized according to format and content. Engagement was measured using an index that aggregates Instagram’s main metrics. The results show that videos, es pecially reels, are the predominant format and the one that generates the most en gagement, following current trends in fast media consumption. In terms of content, cultural topics showed the highest engagement, although a significant influence from one specific profile was identified in this regard. The field of History had the highest volume of posts and the highest average engagement, reflecting greater professional ization and posting frequency among these communicators. It is concluded that en gagement in Humanities-related content on Instagram depends on multiple factors, including format, content, number of followers, and mastery of the platform’s algorith mic dynamics. The research indicates potential for the expansion of science commu nication in Sociology, Geography, and Philosophy and suggests that future studies investigate audience reception and broaden the sample analyzed.
The humanities on social media: using Instagram as a tool for science communication
Keywords: Divulgação científica; Educação não formal; Redes sociais; Ciencias humanas; Scientific dissemination; Non-formal education; Social media; Human sciences; CIENCIAS HUMANAS